INOVASI PEMBELAJARAN BAHASA INGGRIS BERBASIS DIGITAL PICTURE BOOKS UNTUK PEMBELAJARAN JARAK JAUH: DIGITAL PICTURE BOOKS - Eva Dwi Yanti; Ine Rahayu Purnamaningsih (Universitas Singaperbangsa Karawang, 2021)
According to Permendikbud Number 15 of 2020, to prevent the spread and transmission of Covid-19, classroom learning is shifted to distance learning by utilizing digital-based technology. One of them is by using Digital Picture Books as a means of learning English, especially for young learners. However, with the rapid advancement of information and communication technology, it is a challenge for teachers to be careful in selecting digital books that match the criteria in the purpose of learning English. To answer these problems, this paper discusses how to use digital books for distance learning, especially for young English learners or teachers and parents as well as popular genre that can help the teaching and learning process become more effective and efficient. So that its use becomes something more than just a book, namely as a medium in improving English learning in distance learning. The research uses the literature study method by utilizing sites related to this paper.